Can peace building change the way engineering and science are taught? - Rodríguez-Camargo, Christian David (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The way in which engineering and sciences are taught is a topic that has been repeatedly and widely discussed in academic, research, industrial and business spheres, among others. The relevance of the person recently graduated from a career in engineering or science and their attitudes according to local needs have sparked debates that end up questioning even the epistemological and philosophical foundations of the type of scientific and technological knowledge that is being taught and generated in contexts of the so-called global south [1]. It is precisely in this direction that several Latin American thinkers have concluded that the positivist epistemological structure, inherited from the West, may not be so appropriate for achieving the social, political, and economic results that generate the necessary transformations in Latin America that promote the reduction of inequality, the expansion of equal opportunities and the mitigation of environmental impacts generated by purely extractive economies, typical of the countries of the so-called third world.